Efektivitas Murottalal-Qur’an Dan Aromaterapi Inhalasi Lemon Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif - Sri Rohmah; Resi Galaupa (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Childbirth is the process of expulsion of the fetus that occurs at full term of pregnancy (37-42 weeks) born spontaneously with a back of the head presentation, without complications for both mother and fetus. In 2018, 63% of mothers did not know about the preparations that had to be made to reduce labor pain. As an effort to treat labor pain, many methods were used, such as pharmacological and non-pharmacological methods. One of the many non-pharmacological efforts to do is touch or by listening to music. Research Objectives: Knowing the effect of murottalal-quran and lemon inhalation aromatherapy on the intensity of labor pain in the active phase of the first stage of labor at PMB Mimi Nurkomariah. Research Method: quasy experimental design with a pretest-posttest one group design. Samples were birth mothers who were recorded in the report at PMB Mimi Nurkomariah as many as 30 samples using a purposive sampling technique. Bivariate analysis using the Wilcoxon Signed Rank Test. Results: The results of a univariate study on the level of maternal pain before administration of murottalal-qur'an and lemon inhalation aromatherapy were mothers who experienced severe pain, namely 20 people (66.67%) and those who experienced moderate pain, namely 10 people (33.33%) and after administration murottalal-qur'an and lemon inhalation aromatherapy, mothers experienced moderate pain, namely 17 people (56.67%) and those who experienced mild pain, namely 13 people (43.33%). The results of the bivariate study obtained a p value = 0.000. Conclusions and Suggestions: There is the effect of murottalal-quran and lemon inhalation aromatherapy on the intensity of labor pain during the first active phase of PMB Mimi Nurkomariah. It is expected that mothers in labor always prepare themselves for labor pain and use methods that make the mother feel calm in facing labor.